Diversity and DMS(P) - Related genes in culturable bacterial communities in Malaysian coastal waters - Kuek, Felicity W.I; Aazani, Mujahid; Lim, Po Teen; Leaw, Chui Pin; Moritz, Müller (Penerbit Universiti Kebangsaan Malaysia, 2016)
Little is known about the diversity and roles of microbial communities in the South China Sea, especially the eastern region. This study aimed to expand our knowledge on the diversity of these communities in Malaysian waters, as well as their potential involvement in the breakdown or osmoregulation of dimethylsulphoniopropionate (DMSP). Water samples were collected during local cruises (Kuching, Kota Kinabalu, and Semporna) from the SHIVA expedition and the diversity of bacterial communities were analysed through the isolation and identification of 176 strains of cultured bacteria. The bacteria were further screened for the existence of two key genes (dmdA, dddP) which were involved in competing, enzymatically-mediated DMSP degradation pathways. The composition of bacterial communities in the three areas varied and changes were mirrored in physico-chemical parameters. Riverine input was highest in Kuching, which was mirrored by dominance of potentially pathogenic Vibrio sp., whereas the Kota Kinabalu community was more indicative of an open ocean environment. Isolates obtained from Kota Kinabalu and Semporna showed that the communities in these areas have potential roles in bioremediation, nitrogen fixing and sulphate reduction. Bacteria isolated from Kuching displayed the highest abundance (44%) of both DMSP-degrading genes, while the bacterial community in Kota Kinabalu had the highest percentage (28%) of dmdA gene occurrence and the dddP gene responsible for DMS production was most abundant (33%) within the community in Semporna. To the best of our knowledge, this is the first study looking at the diversity of culturable bacteria in coastal waters of East Malaysia and also their potential roles in the DMS(P) cycle.